Fabrication and Characterisation of Nanoscale Ni-CGO Electrode from Nano-Composite Powders. (10th July 2019) - Chen, Jingyi; Ouyang, Mengzheng; Boldrin, Paul; Liu, Xinhua; Darr, Jawwad; Atkinson, Alan; Brandon, Nigel P
Abstract : Incorporating nanoparticles into SOC electrode is a viable method to improve the electrochemical performance. In this work, nanoparticles of NiO and gadolinia-doped ceria (CGO) approximately 10 nm in diameter fabricated using a continuous hydrothermal flow synthesis are made into nano-structured SOC fuel electrodes via mixing and co-sintering. Both the Ni and CGO are of 50-100 nm in diameter in the final electrode. FIB-SEM 3-D tomography is carried out on the nanoscale Ni-CGO electrode which has been aged for 70 h, showing a high active triple phase boundary density of 3 µm -2 and a high active double phase boundary density of 2 µm -1 . The total polarisation resistance of the electrode is stable at 0.20 Ω cm 2 under open circuit conditions at 800 °C annealing in humidified 5% H2 -N2 .